The generation of identity in late medieval hagiography : speaking the saint - Ashton, Gail, 1957- (Routledge research in medieval studies, 2000)
In this interdisciplinary and boundary breaking study, Gail Ashton examines the depiction of female saints in a wide range of medieval texts.